Placental chorioangiomatosis: a case report and literature review - Wu, Xixi; Cheng, Linbo; Zhang, Shimao; Lu, Yu; Wang, Tao; Su, Mi; Yuan, Qinqin; Ge, Huisheng (Frontiers in Pediatrics, 2025)
The placenta is a highly specialized temporary organ during pregnancy. As the hinge of material exchange between mother and fetus, it plays a crucial role in maintaining the fetus's intrauterine life and growth period of fetus. Placental lesions or dysfunction can cause pregnancy diseases. Placental chorioangioma is a benign tumor originating from the placental with an incidence rate of 1%, whose etiology has not yet been fully elucidated. Prenatal diagnosis can usually be done by clinical ultrasound. However, placental chorioangiomatosis, as a placental choriovascular disease, is rarely reported or studied at home and abroad. Due to the unclear etiology and pathogenesis, prenatal diagnosis of placental chorioangiomatosis before early recognition of severe maternal and fetal complications during pregnancy is sparse. Therefore, patients cannot be effectively treated, and pregnancy outcomes are often poor. Herein we provide a case at our hospital and conduct a series of literature reviews around this case to further improve the understanding of placental chorioangiomatosis, and promote early recognition and early intervention.